FROM THE EDITOR = Redaksioneel - Lategan, Bernard C. (Scriptura, 1985)
In this issue the emphasis falls on questions of a hermeneutical nature. In the first article the nature of man’s knowledge of the truth is discussed. The hypothesis, that truth is neither absolute, nor relative, but that it should rather be described as ‘relational’, is illustrated with reference to two well-known "Introductions" to the New Testament: those of Kümmel and of Guhtrie. The second contribution deals with a subject from the Old Testament: it explains how archaeological discoveries of the 20th century, especially those at Ras Shamra, have yielded new information which has improved the understanding and translation of a text like the oracles of Jeremiah. The last article contains an interesting perspective on an evergreen challenge to the preacher, namely the Christological interpretation of the Old Testament.